A normal genetic variation modulates synaptic MMP‐9 protein levels and the severity of schizophrenia symptoms. Issue 8 (16th June 2017) - Lepeta, Katarzyna; Purzycka, Katarzyna J; Pachulska‐Wieczorek, Katarzyna; Mitjans, Marina; Begemann, Martin; Vafadari, Behnam; Bijata, Krystian; Adamiak, Ryszard W; Ehrenreich, Hannelore; Dziembowska, Magdalena; Kaczmarek, Leszek
Abstract: Matrix metalloproteinase 9 (MMP‐9) has recently emerged as a molecule that contributes to pathological synaptic plasticity in schizophrenia, but explanation of the underlying mechanisms has been missing. In the present study, we performed a phenotype‐based genetic association study (PGAS) in > 1, 000 schizophrenia patients from the Göttingen Research Association for Schizophrenia (GRAS) data collection and found an association between the MMP‐9 rs20544 C/T single‐nucleotide polymorphism (SNP) located in the 3′untranslated region (UTR) and the severity of a chronic delusional syndrome. In cultured neurons, the rs20544 SNP influenced synaptic MMP‐9 activity and the morphology of dendritic spines. We demonstrated that Fragile X mental retardation protein (FMRP) bound the MMP‐9 3′UTR. We also found dramatic changes in RNA structure folding and alterations in the affinity of FMRP for MMP‐9 RNA, depending on the SNP variant. Finally, we observed greater sensitivity to psychosis‐related locomotor hyperactivity in Mmp‐9 heterozygous mice. We propose a novel mechanism that involves MMP‐9‐dependent changes in dendritic spine morphology and the pathophysiology of schizophrenia, providing the first mechanistic insights into the way in which the single base change in the MMP‐9 gene (rs20544) influences gene function and results in phenotypic changes observed in schizophrenia patients. Synopsis: A single‐nucleotide polymorphism rs20544 located in the 3′ untranslated region of the MMP‐9 gene modulates synaptic MMP‐9 protein levels and contributes significantly to the chronic delusional syndrome in schizophrenia patients. rs20544 MMP‐9 gene polymorphism markedly affects delusional symptoms in schizophrenic patients, without influencing overall susceptibility to the disease. rs20544 polymorphism influences synaptic MMP‐9 activity and the morphology of dendritic spines. rs20544 polymorphism affects MMP‐9 mRNA structure and the affinity of FMRP binding to MMP‐9 mRNA. lower levels of MMP‐9 in the brain in Mmp‐9 heterozygous mice resulted in greater sensitivity to psychosis‐related locomotor hyperactivity. Abstract : A single‐nucleotide polymorphism rs20544 located in the 3′ untranslated region of the MMP‐9 gene modulates synaptic MMP‐9 protein levels and contributes significantly to the chronic delusional syndrome in schizophrenia patients.